2006
DOI: 10.1002/pssb.200642289
|View full text |Cite
|
Sign up to set email alerts
|

First‐principles study on the elastic properties and electronic structure of TiNi‐based ternary shape memory alloys

Abstract: TiNi-based shape memory alloys have been widely used in the fields of engineering and medicine due to their shape memory effect and superelasticity, which are displayed during martensitic transformations [1]. However, the martensitic transformation in this system is least understood compared with other systems due to the complexity of the transformation and sensitivity to alloying addition. It is well known that most TiNi-based alloys have an ordered B2 phase at high temperatures and transform to a stable low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Very recently, we experimentally found that low addition of Ce in TiNi increases the martensitic transformation tem- 6.25 have been calculated in our previous work [17]. The results show that the shapes of all total DOS curves are similar and all of them comprise two sets of peaks separated by a dip.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…Very recently, we experimentally found that low addition of Ce in TiNi increases the martensitic transformation tem- 6.25 have been calculated in our previous work [17]. The results show that the shapes of all total DOS curves are similar and all of them comprise two sets of peaks separated by a dip.…”
Section: Resultsmentioning
confidence: 67%
“…Higher stability corresponds to lower total DOS value at the Fermi level. In addition, our previous work [17] shows that the total DOS at the Fermi level is primarily offered by the Ti d DOS. Thus we conclude that higher stability corresponds to lower Ti d DOS value at the Fermi level.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It is known that the stability of Ti-based B2 phase compounds are determined by the Ti d-states at Fermi level. In Ti-based compounds, higher stability corresponds to a lower Ti d DOS value at the Fermi level [18]. The higher stability of Ti 43.75 Pd 50 X 6.25 can be attributed to the decrease in the density of d states of Ti and X at Fermi level with increasing atomic number of X impurities.…”
Section: A Structural Propertiesmentioning
confidence: 99%
“…At high temperatures, TiNi-based alloys possess an ordered B2 austenitic phase that transforms to a stable lower-temperature martensitic phase as the temperature drops. The parent B2 phase changes into a monoclinic B19′ martensite in TiNi alloy [3]. The high-temperature state is frequently a 𝛼𝛼-phase with a body-centred cubic (bcc) structure, whereas the lower temperature phase has a hexagonal close packed 𝛽𝛽 martensitic structure, given this, a metallic composition which will exist in the primitive 𝛽𝛽 -phase at ambient temperatures must be chosen [4].…”
Section: Introductionmentioning
confidence: 99%